Assessment of micro-cogeneration network in European mining areas: A prototype system. (1st May 2019) - Paredes-Sánchez, J.P.; Míguez, J.L.; Blanco, D.; Rodríguez, M.A.; Collazo, J.
Abstract: The limited success in the promotion of biomass use through technologically advanced heating networks in economically depressed areas has been, in part, attributed to the insufficient understanding of the transformation patterns of the energy for use of indigenous resources. In this regard, Organic Rankine cycle (ORC) is proved to be reliable technology that can efﬁciently convert resources into useful power by thermal machines. The present study has the aim to study the conversion of energy by implementing a district micro-cogeneration system using Organic Rankine Cycle (ORC) technology in mining areas. For this purpose, the region of Valdeorras (Spain) has been selected as a study area based on the functional character of its mining area. The methodology used allows for analysis of the resource, technology and the management of the conversion of energy during the different phases in a process of analytical hierarchy. Additionally, a nodal macro network is set in the study area that covers part of the electrical as well as thermal demand with indigenous resources. The nodal micro-cogeneration unit operates by heat-match mode and generates electricity and heat, 200 kWe and 1.9 MWth, respectively, by supply of 2.6 MWth by biomass combustion. Highlights: An innovative solution by nodal network of district heating is defined. The implementation of units of micro-cogeneration in nodes can be achieved. The feasibility of exploiting the bioenergy through micro-cogeneration is analysed. The defined energy systems produce economic, social and environmental benefits.